INDIKASI KECANDUAN SMARTPHONE PADA REMAJA DI SURABAYA - Abdul Fauzi; Titis Eka Apriliyanti; Masmuhul Khoir; Antonia Helena Hamu (Akademi Keperawatan Dharma Husada Kediri, 2020)
Introduction: Smartphone addiction is a problem that often occurs in early adolescents. The purpose of this study was to find an overview of smartphone addiction indications in adolescents. Methods: The population in this study is junior high school students in Surabaya who have smartphones. Sampling was carried out using multistage random sampling in ten schools spread in each region in Surabaya and each region represented by a private school and one public school. The number of samples in the study was 400 students. Measurement using Smartphone addiction Scale (SAS). Result: The sample in this study were 400 students with 30.5% male and 69.5% female. The sample was between 12-17 (mean, 14.03 + 0.813) years with a distribution of 13% class seven, 65.8% class eight and 21.2% class Nine. The four indicators showed the majority in the moderate category, namely life disturbance, positive anticipation, withdrawal and cyberspace oriented, while overused and tolerance are mostly in the lower category. Conclusion: Cyberspace oriented is the most visible indication because smartphones are considered an important part of adolescents' lives. So eventhough the use of a long smartphone is not considered excessive. Identification of the type of addiction and the time that smartphone usage needs to be added as additional data.